Restored clearance of senescent neutrophils by tissue-resident macrophages limits organ aging - Yuting Jessy Tan; Travis E. Conley; Fuwen Yao; Fernando J. García-Marqués; Damilola E. Akinyemi; Van Vuong Dinh; Qian Wang; Abel Bermudez; Jieun Kim; Julia A. Belk; Oliver Soehnlein; Sharon J. Pitteri; et al. (Science, 2026)
Aging disrupts tissue homeostasis across organ systems. Here, we identify tissue-resident macrophages (TRMs) as central coordinators of age-related organ decline through impaired clearance of senescent neutrophils, a process regulated by the immunomodulatory prostaglandin E2 (PGE 2 ) receptor EP2. Reducing TRM EP2 signaling in aged mice preserved youthful mitochondrial fitness and prevented cognitive decline, frailty, sarcopenia, adiposity, cardiac impairment, and systemic inflammation. Plasma proteomics implicated the liver as a major source of age-associated immune change, in which reduced TRM EP2 signaling rescued neutrophil efferocytosis and prevented paracrine stress in neighboring cells. Elevated TRM EP2 expression and senescent neutrophils were also observed in aged and diseased human tissues. Pharmacologic EP2 inhibition restored youthful neutrophil clearance, establishing impaired TRM efferocytosis as a reversible driver of organ decline in aging.